ANALISIS KELAYAKAN USAHA PENGOLAHAN SAGU BASAH DI PAPUA - Cynthia Iskowanto; Felecia Felecia (Jurnal Titra, 2021)
Sago is a common food consumed by Papuans living in coastal areas. Sago is usually used for household consumption and sold in traditional markets. The Department of Industry, Trade, Cooperatives, SME & Manpower, Papua Province has a program to help small industries in Papua. A feasibility test will be conducted to determine whether the Wet Sago Processing Business is feasible or not. There are three parameters used in this test, which is market feasibility, technical feasibility, and financial feasibility. Market feasibility will be evaluated from the SPT (segmentation, position, and target). Technical feasibility will be seen from operational management, production process, production location, and production layout. Financial feasibility will be assessed through the payback period, NPV, and IRR. From the the research,  it is known that the wet sago processing business in Papua is feasible if the capacity is increased by adding the sedimentation facilitiy